Monoclonal antibodies: formulations of marketed products and recent advances in novel delivery system. (3rd April 2017) - Cui, Yanan; Cui, Ping; Chen, Binlong; Li, Suxin; Guan, Hua
Abstract: Monoclonal antibodies (mAbs) are extensively employed for disease diagnosis and treatment because of their high homogeneity and antigen specificity. In recent years, important outcomes have been achieved with mAbs due to their admirable therapeutic efficacy and relatively rare side effects. In clinical practice, several mAb products have been approved by regulatory entities, but their formulations have been highly specific given the complex structure and proteinaceous nature of mAbs. Thus, more attention has been given on formulations. An increasing number of novel delivery systems have been exploited to optimize the application of mAbs. In this article, the formulations, dosages, origins and administration routes of available mAbs approved by the Food and Drug Administration (FDA) are summarized and categorized. Key issues involved in formulation, processing and storage are addressed as well as other challenges in achieving effective mAb delivery. Finally, recent advances in delivering mAbs in their most bioavailable forms are also briefly reviewed.